Digitalisation Anxiety in Czech Industrial Workplaces: A Multilevel Qualitative Study - Nechvatal, Marek; Sencik, Josef; Vesela, Katerina; Mraz, Vaclav; Stepanek, Martin (Society and Economy in Central and Eastern Europe, 2026)
Digitalisation is reshaping industrial work, yet employees’ lived experience determines whether its promised value is realised. Drawing on 66 semi‑structured interviews with employees in Czech industrial workplaces, this study maps overall stance and delineates multilevel triggers of digitalisation‑related anxiety. A large majority expressed a predominantly optimistic view (53/66; 80.3%), while pessimistic (5/66; 7.6%) and ambivalent (8/66; 12.1%) minorities reported concerns. Anxiety clustered at societal (e.g., macro‑uncertainty about employment and safety due to failures), organisational (implementation quality, availability of qualified staff, training and help desks, transparency of data‑driven monitoring) and individual levels (interpersonal frictions, fatigue, sleep disturbance). Across levels, uncertainty emerged as the primary driver, interacting with perceived decision latitude and support. On this basis, we outline actionable interventions: the transparent communication of scope and timelines; participatory implementation to increase discretion; task‑relevant training and competent help desks; team‑level norms that contain communication overload; and individual bounded‑attention routines that reduce techno‑overload. Conceptually, the paper advances a process‑plus‑content perspective on digitalisation anxiety that integrates societal, organisational and individual triggers and clarifies where to target the socio‑technical system. While qualitative and sector‑specific, the findings are transferable rather than statistically generalisable and provide a practical scaffold for designing interventions that sustain employees’ broadly positive orientation while tempering anxiety during ongoing digital change.